Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea) - Ng, Peter K. L.; Rahayu, Dwi Listyo (Zootaxa, 2014)
The family Acidopsidae Števčić, 2005, is revised; and two subfamilies are recognised. The Acidopsinae Števčić, 2005, is characterised by the coxal male opening, a quadrate basal antennal article and vulvae arranged near the median longitudinal thoracic sternal groove. Three genera are included in the Acidopsinae: Acidops Stimpson, 1871 (with two species), Parapilumnus Kossmann, 1877 (with two species) and Crinitocinus gen. nov. (monotypic for Pilumnus alcocki Borradaile, 1902). The Raouliinae Števčić, 2005 (= Typhlocarcinodidae Števčić, 2005; Caecopilumnidae Števčić, 2011), is characterised by its coxo-sternal male opening, a short basal antennal article which is distinctly wider than long and vulvae arranged submedially on thoracic sternite 6. Four genera are included in the Raouliinae: Raoulia Ng, 1987 (with five species, three of which are described as new), Caecopilumnus Borradaile, 1902 (with three species of which one is described as new), Typhlocarcinodes Alcock, 1900 (monotypic) and Thecaplax gen. nov. (for one new species).